Shifts in the Distribution and Fate of Sedimentary Polycyclic Aromatic Hydrocarbons Within the Estuarine‐Inner Shelf Areas of the East China Sea: Response to Human‐Induced Catchment Change. Issue 1 (20th January 2020) - Wang, Chenglong; Hao, Zhe; Feng, Ziyue; Zhang, Chuchu; Li, Yali; Yu, Wenwen; Zou, Xinqing
Key Points: Distribution patterns of PAHs changed drastically due to human‐induced catchment changes Depositional center of PAHs in the ECS transferred southward River‐dominated margins will face this threat worldwide Abstract: Human‐induced changes in river catchments, such as damming, can affect estuarine depositional settings and further affect the transport of sediments and associated pollutants. Polycyclic aromatic hydrocarbons (PAHs) in surface sediments from the East China Sea (ECS) at two time nodes (2006 and 2018) were compared to understand the response of PAHs to human‐induced catchment changes. PAH concentrations in the ECS ranged from 8–414 ng g −1 (dry weight), with a mean value of 112 ± 77 ng g −1, relatively low than that in 2006 (38–308 ng g −1, with a mean of 122 ± 60 ng g −1 ). Sharp decreases in sediment loads have triggered erosion in subaqueous delta and changed the distribution of sediment components, which may eventually influence the distribution pattern of PAHs. The obvious spatial differentiation of PAHs between 2006 and 2018 suggested that the depositional center of PAHs shifted from the estuary to the inner shelf area. PAH deposition patterns in the ECS were primarily influenced by riverine input before 2006 but are now dominated by winnowing processes related to long‐distance transport due to sharply decreased sediment loads. Dam construction in the river catchment intercepted large amounts of sediments and PAHs, shifting the Changjiang‐derived PAH depositional center from the ocean to reservoirs. Overall, depositional patterns of PAHs in the ECS were largely altered by human‐induced catchment changes, which may cause significant impacts on the region's biogeochemical cycles and ecosystem health. Plain Language Summary: Coastal oceans are usually considered important sinks of terrestrial materials, especially river‐dominated coastal margins. However, river‐derived terrestrial materials have decreased drastically in the last several decades worldwide, due to intensified human activities that have changed the local sedimentary environment. In this study, changes in the surface sediment grain size within the East China Sea from 2006 to 2018 indicated that the sedimentary environment in this region was clearly altered. Similarly, the distributions and compositions of PAHs in surface sediments changed from 2006 and 2018. Based on combined analysis of grain size and PAHs, we found that PAH dynamics in this region were primarily influenced by riverine inputs before dam construction in the Changjiang (Yangtze) River basin but are now dominated by winnowing processes related to long‐distance transport due to sharply decreased sediment loads. Therefore, intensified human‐induced catchment changes have significant influenced the fate of PAHs in the East China Sea.